KEANEKARAGAMAN IKAN DAN POTENSI EKOWISATA BAHARI BERBASIS SOSIAL EKONOMI (STUDI KASUS KALI BIRU BANABUNGI, KABUPATEN BUTON) - Prima Insamilandari Syah; Ananta Wira Pratama; Suhaiba Djai; Wa Ode Purnama; Nurnila Nurnila; Izhardin Izhardin (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
Marine ecotourism is an alternative form of tourism development that not only prioritizes nature conservation but also considers the socioeconomic welfare of coastal communities. This study examines the potential and challenges of developing socioeconomic-based marine ecotourism in Kali Biru Banabungi, Buton Regency, using a SWOT analysis approach. This tourist area has abundant fishery biodiversity, including various fish genera that reflect the health of the aquatic ecosystem. This potential can be a major attraction for tourist activities such as snorkeling and diving, which also support marine conservation. However, the management of ecotourism in this area requires attention to various challenges, such as limited infrastructure, waste management, and the quality of human resources that still needs to be improved. Through SWOT analysis, this study identifies the strengths of Kali Biru Banabungi, such as its captivating natural scenery, diversity of fish fauna, and good accessibility. On the other hand, the detected weaknesses are the lack of supporting facilities and suboptimal cleanliness management. The existing opportunities include support from the local community and government regulations that support the development of tourist areas, while the threats faced include damage to facilities and competition with other tourist attractions. The proposed ecotourism development strategy includes optimizing the potential of biodiversity and cooperation between the local community, government, and tourism managers. This approach is expected to ensure the sustainability of marine ecotourism that benefits nature conservation and community economic empowerment.